2016
DOI: 10.1002/adfm.201505175
|View full text |Cite
|
Sign up to set email alerts
|

A Triple‐Collaborative Strategy for High‐Performance Tumor Therapy by Multifunctional Mesoporous Silica‐Coated Gold Nanorods

Abstract: To integrate treatments of photothermal therapy, photodynamic therapy (PDT), and chemotherapy, this study reports on a multifunctional nanocomposite based on mesoporous silica‐coated gold nanorod for high‐performance oncotherapy. Gold nanorod core is used as the hyperthermal agent and mesoporous silica shell is used as the reservoir of photosensitizer (Al(III) phthalocyanine chloride tetrasulfonic acid, AlPcS4). The mesoporous silica shell is modified with β‐cyclodextrin (β‐CD) gatekeeper via redox‐cleavable P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(87 citation statements)
references
References 77 publications
0
87
0
Order By: Relevance
“…Therefore, vascular endothelial cell was chosen to evaluate the cytocompatibility of the designed delivery system. As shown in Figure S4 (Supporting Information), compared with controlled group, the proliferation of cells treated with Tet, Au@MSNs, and Tet@Au@MSNs was effected slightly for 3 d, it suggested that the elements of this designed system possessed acceptable cytocompatibility, which corresponded to the results of previous reports …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, vascular endothelial cell was chosen to evaluate the cytocompatibility of the designed delivery system. As shown in Figure S4 (Supporting Information), compared with controlled group, the proliferation of cells treated with Tet, Au@MSNs, and Tet@Au@MSNs was effected slightly for 3 d, it suggested that the elements of this designed system possessed acceptable cytocompatibility, which corresponded to the results of previous reports …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, GNR can effectively absorb NIR light by its longitudinal surface plasmon resonance. The NIR light can deeply penetrate tissues without damaging normal tissues due to their weakly absorption by tissues and blood [16,17]. There-fore, GNR is a promising agent for the combined advantages of photoacoustic imaging and photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Osteolytic bone metastases/invasion were clearly observed in the pubis and ischium of PBS-treated mice (Fig. 5i) 32 . In aPDL1-treated mice, the slight lysis of pubis was observed.…”
Section: T1mentioning
confidence: 93%